Perilaku Seksual Berisiko pada Pedagang Bawang Merah di Kecamatan Wanasari Kabupaten Brebes - Nina Maria Desi; Zahroh Shaluhiyah; Sutopo Patria Jati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: Along with the times, the population at high risk of sexually transmitted infections increase rapidly. From a preliminary study in the district Wanasari Brebes revealed that their knowledge about sexual behavior said to be low risk and lots of sexual risk behavior without condom.Method: This research is descriptive quantitative analytical with cross-sectional design study, methods for collecting the data by distributing questionnaires to find a picture on the risky sexual behaviors of respondent. The sample in this research is 120 people.Results: 86,7% respondent has risky sexual behavior. 70,8% of respondent is above 32 years old with low education as much as 57,5% and not marriage yet 52,5%. 61,7% of respondent has risky behavior in their leisure time. Variables that significantly relationship against sexual behavior are ages and leisure activity.based on multivariate analisys, variables that strongly connected to sexual behavior is ages, leisure activity, and religiousity. Advice given to Departemen Kesehatan Brebes for further enhance the knowledge of onion traders in terms of risky sexual behavior, include facilitating spare time with things that are more useful to avoid risky sexual behavior.Keyword : Behavior, sexual risk, Brebes